Assisted suicide for prisoners: An ethical and legal analysis from the Swiss context. (18th January 2022) - Della Croce, Yoann
Abstract: Should prisoners be allowed to access assisted suicide? Whereas the ethical and legal issues regarding assisted suicide have now been extensively discussed in the literature, surprisingly scarce attention has been given to the pressing issue of inmates requesting assistance in dying. Through an analysis supported by the Swiss legal framework, I first argue that the principle of equivalence in prison medicine, which states that prisoners ought to receive the same level of health care as the general population does not prove a solid basis in arguing for prisoners' right to assisted suicide. Over the course of the paper, I defend the view that the right to access assisted suicide is to be understood as a liberty that cannot be removed from incarcerated individuals. I argue that removing such a liberty cannot be consistently held within a legal framework where the death penalty does not exist, for doing so necessarily forgoes the State's ability to decide on when and how prisoners' lives end, in turn necessarily leaving them the liberty to end theirs when they decide so. I finally argue against the position that the capacity for autonomous choice is lacking in inmates by disentangling the particular features of the prison‐setting and show that the context of incarceration is not so substantially different from regular cases of suicide assistance that it warrants a difference in treatment. The position I propose proves important in order to both respect prisoners' rights and ensure they retain a minimum level of control over their existences.